Implementasi Pendidikan Agama Kristen (PAK) Masa Yesus di Sekolah - Sitompul, Baginda; Manalu, Afriani; Sihombing, Grace Metaria; Ziraluo, Dasriana (LP. Ma'arif Janggan Magetan, 2023)
In the Bible there is a lot of information that writes down the teachings that Jesus did. The fruit of Jesus' teaching is proof that He is a teacher who has a personality, broad insight, role model, both from His words and deeds. The works of Jesus are inseparable from the culture of learning that has been carried out since he was young. This is one factor that makes Him appear as the Great Teacher. After finishing studying from school, Jesus taught with creative and effective methods for His followers. For this reason, in the context of Christian Religious Education (PAK) which is taught in formal schools, it is necessary to refer to Christian Religious Education at the time of Jesus, so that the principles of Christian Religious Education in schools can be specifically maintained from time to time. The researcher will explain how Christian Religious Education was when Jesus was a Jewish boy, starting with His education in the midst of the family, education at Beit Safar, education at Beit Talmud, education at the Beit Midrash stage, to the implementation of Christian Religious Education in schools today. The purpose of writing is to study Christian Religious Education at the time of Jesus in schools and the implementation of Christian Religious Education in formal schools. The method used in writing is a qualitative research method with literature as the main source.